University of the West Indies: unlocking the potential of the Region: (Caribbean development in light of global trends) - Carrington, Edwin W. (Caribbean Community Secretariat GeorgetownGY, 1993)
Looks at the role played and the contribution made by the University of the West Indies in Caribbean development. Examines global trends as well as certain trends which hold specific relevance for the Caribbean e.g. the diversion of foreign capital resources from Third World countries like the Caribbean to those of Eastern Europe; the decline of preferential market access. Proposes that in order for the Caribbean to secure a place in the future expanding world of mega blocs, Caribbean development would require major shifts in thinking and attitude in perception of the world, in education and training, in organisation and in production.